« hedera » platform: Research data management platform for the preservation and dissemination of open linked data - CAZEAUX, Hugues; VONLANTHEN, Mathieu (Revue électronique suisse de science de l’information (RESSI), 2025)
« hedera » is an active research data management platform based on linked data principles developed by the University of Geneva. It is mainly dedicated to the preservation and dissemination of Linked Open Data. The main objective of « hedera » is to offer a centralized and unified system to avoid data fragmentation and data losses often encountered by researchers working in siloed, purpose-built, small-scale infrastructures. Data can be imported from existing archives or from another active data platform, in two different forms: metadata import (XML, JSON, CSV) and import of research data files (e.g., images, sound, video, PDF files).